The level of awareness zakat obligations among staff at Department of Islamic Religion Pahang (JAIP) / Muhammad Amirul Firdaus Aziz - Aziz, Muhammad Amirul Firdaus (2025)
Zakat is the pillar of the Islamic faith, representing an important mechanism for fostering social equality and reducing poverty in Muslim societies. As one of the five pillars of Islam, zakat is a mandatory obligation for eligible Muslims, aimed at redistributing wealth to support the less fortunate. This study aimed to identify knowledge gaps or misconceptions about zakat, measure the importance of fulfilling zakat obligations by the Department of Islamic Religious Pahang (JAIP) employees, and examine the level of awareness of zakat obligations among JAIP employees. This study used a quantitative approach, with data collected through a questionnaire distributed to 103 JAIP employees. The analysis identified factors such as lack of awareness, distrust of zakat management, and the influence of materialistic culture. The data collected was analyzed using the Statistical Package of Social Science (SPSS) to determine the relationship between these factors. This study also proposed solutions such as religious education, training, and awareness programs to increase staff understanding of the importance of zakat. The results of the study provide useful insights to strengthen zakat management, increase community trust, and support the socio-economic development of the Muslim community.